Molecular Dynamic Study and Synthesis of 1H-benzo[d]imidazole-5-carboxamide Derivatives as Inhibitors for Yellow Fever and Zika Virus Replication - Madonna M. A. Mitry (Ain Shams University, 2020)
Flaviviridae family comprises the flavivirus genotype that represents a significant world health problem as it includes the Yellow fever virus (YFV) and Zika virus (ZIKV) which are responsible for large outbreaks and for which novel therapies are in urgent demand. The benzimidazole scaffold has been widely reported for its antiviral activity, and hence a new series of 1H-benzo[d]imidazole-5-carboxamide derivatives (VIIa-x, VIIIa-h & IXa, b) was designed, synthesized, and biologically evaluated for their antiviral activity. 5 Compounds (VIId, VIIe, VIIh, VIIn and VIIt) showed antiviral activity against YFV in the low micromolar range using the human hepatoma Huh-7 cells and Vero cells. One compound (VIId) exhibited activity on both YFV (EC50=1.7 ± 0.8µM) and ZIKV (EC50=4.5 ± 2.1µM). Molecular docking and molecular dynamics simulation studies were conducted to understand the SAR of newly synthesized compounds, to explore the potential target of compound VIId and to investigate the possible binding mode to its target.